Principal's Leadership Contribution And Work Motivation On Teacher's Work Discipline State Vocational School Of Padang City - Muhammad Arif Kurnianda; Nellitawati; Sufyarma M; Sulastri (CV. AFDIFAL MAJU BERKAH, 2022)
Based on the pre-survey in the field, it is illustrated that the work discipline of Padang City State Vocational School teachers is still not good. This is thought to have something to do with the principal's leadership and the work motivation of teachers. Therefore, it is necessary to conduct research to test its validity. This study aims to reveal the contribution of principals' leadership and work motivation to the work discipline of Padang City State Vocational High School teachers. The hypotheses proposed in this study are: (1) principal leadership contributes to teacher work discipline, (2) work motivation contributes to teacher work discipline, (3) principal leadership and work motivation jointly contribute to teacher work discipline. The population in this study were all teachers of State Vocational Schools in Padang City, amounting to 277 people. The research sample amounted to 78 people who were taken with the Stratified proportional random sampling technique, taking into account the strata of the service period. The research instrument used is a rating scale and a Likert Scale model questionnaire that has been tested for validity and reliability. The research data were analyzed by correlation and regression techniques. The results of data analysis show that: (1) principal leadership contributes to teacher work discipline by 28%, (2) work motivation contributes to teacher work discipline by 22. 7%, (3) principal leadership and work motivation together contribute to the work discipline of teachers by 47. 3%. The achievement level of teacher work discipline scores of 91. 34% is in the very high category, and for principals' leadership 88. 14% is in the good category while for teacher work motivation is 87. 27 of the ideal score is in the high category. The findings above imply that the principal's leadership and work motivation are two factors that can improve teacher work discipline, in addition to other factors.